Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.685
|View full text |Cite
|
Sign up to set email alerts
|

When Modern Technologies Meet Ageing Workforces: Older Workers are more affected by Demands from Mobile Interruptions than their Younger Counterparts

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…When attended to, demand appraisals have been explained primarily through one of three theoretical lenses (transactional theory of stress, P-E fit theory and cybernetic theory), in which individuals perform a subjective evaluation of their environment in terms of opportunity or threat (D'Arcy et al, 2014(D'Arcy et al, , 2018Galluch et al, 2015;Liang et al, 2019), (mis)fit (Ayyagari et al, 2011;Stich et al, 2019b;Chilton et al, 2005), or (in) equilibrium (Stich et al, 2019a) However, what has lacked the most attention is the explanation of the factors that may influence the demand appraisal process for cybersecurity professionals and how certain factors are more influential than others, creating a challenge or hindrance perception of demand. Some early research suggests that age, gender and personality differences can play an influential role in the stress process, but we have an underdeveloped understanding of how these differences affect cybersecurity professionals' appraisal of demands (Ragu-Nathan et al, 2008;Tams et al, 2017;Srivastava et al, 2015;Maier et al, 2019;Hwang and Cha, 2018;Lazarus and Folkman, 1987). Most research that has considered individual differences has shown how these differences affect the overall experience of stress but not the influence on the appraisal process itself, but cybersecurity professionals are a unique breed of IT professional (Cobb, 2016;Bashir et al, 2017) (Tarafdar et al, 2019).…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…When attended to, demand appraisals have been explained primarily through one of three theoretical lenses (transactional theory of stress, P-E fit theory and cybernetic theory), in which individuals perform a subjective evaluation of their environment in terms of opportunity or threat (D'Arcy et al, 2014(D'Arcy et al, , 2018Galluch et al, 2015;Liang et al, 2019), (mis)fit (Ayyagari et al, 2011;Stich et al, 2019b;Chilton et al, 2005), or (in) equilibrium (Stich et al, 2019a) However, what has lacked the most attention is the explanation of the factors that may influence the demand appraisal process for cybersecurity professionals and how certain factors are more influential than others, creating a challenge or hindrance perception of demand. Some early research suggests that age, gender and personality differences can play an influential role in the stress process, but we have an underdeveloped understanding of how these differences affect cybersecurity professionals' appraisal of demands (Ragu-Nathan et al, 2008;Tams et al, 2017;Srivastava et al, 2015;Maier et al, 2019;Hwang and Cha, 2018;Lazarus and Folkman, 1987). Most research that has considered individual differences has shown how these differences affect the overall experience of stress but not the influence on the appraisal process itself, but cybersecurity professionals are a unique breed of IT professional (Cobb, 2016;Bashir et al, 2017) (Tarafdar et al, 2019).…”
Section: Future Research Opportunitiesmentioning
confidence: 99%